Search for FCNC single top-quark production at √s=7 TeV with the ATLAS detector* - Aad, Georges; Anders, Christoph; Anders, Gabriel; Andrei, George Victor; Davygora, Yuriy; Dietzsch, Thorsten; Geweniger, Christoph; Hanke, Paul; Henke, Michael; Kasieczka, Gregor; Khomich, Andrei; Kluge, Eike-Erik; et al. (Physics letters, 2012)
A search for the production of single top-quarks via flavour-changing neutral-currents is presented. Data collected with the ATLAS detector at a centre-of-mass energy of s=7 TeV, corresponding to an integrated luminosity of 2.05 fb−1, are used. Candidate events with a semileptonic top-quark decay signature are classified as signal- or background-like events by using several kinematic variables as input to a neural network. No signal is observed in the neural network output distribution and a Bayesian upper limit is placed on the production cross-section. The observed upper limit at 95% confidence level on the cross-section multiplied by the t→Wb branching fraction is measured to be σqg→t×B(t→Wb)<3.9 pb. This upper limit is converted using a model-independent approach into upper limits on the coupling strengths κugt/Λ<6.9⋅10−3 TeV−1 and κcgt/Λ<1.6⋅10−2 TeV−1, where Λ is the new physics scale, and on the branching fractions B(t→ug)<5.7⋅10−5 and B(t→cg)<2.7⋅10−4.
ATLAS Collaboration: G. Aad, G. Anders, V. Andrei, Y. Davygora, T.A. Dietzsch, C. Geweniger, P. Hanke, M. Henke, G. Kasieczka, A. Khomich, E.-E. Kluge, A. Kugel, V. Lendermann, R. Maenner, K. Meier, F. Müller, R. Narayan, S. Poddar, S. Schaetzel, V. Scharf, S. Schmitt, A. Schöning, N. Schroer, H.-C. Schultz-Coulon, R. Stamen, M. Wessels [und weitere]
Gesehen am 30.11.2018